Characteristics of Plasma Dynamics in Current Sheets Formed in Helium Plasma - Anna G. Frank (MDPI AG, 2021)
The characteristic features of plasma acceleration in the current sheets are discussed on the basis of an analysis of the structure of electrodynamic forces at successive stages of the evolution of the current sheets formed in the plasma with helium ions. Of particular interest is the generation of reverse currents at the side edges of the sheet and the appearance of forces, which are braking previously accelerated plasma flows.